Multi-agent CHANS: BDI Farmer Intentions and Decision Making (2021)
This paper extends previous works on multi-agent-based simulation models of Coupled Human and Natural Systems (CHANS), by introducing a farmer agent model capable of interact with environmental, economic, and spatial variables in the context of supply and demand of environmental services. Emphasis is made on how the Farmer Agent implements the BDI framework (Believes, Desires, and Intentions) at its core. Also, insights about its decision-making mechanism based on fuzzy logic are provided. Preliminary results are shown in terms of modulating variables such as knowledge, money, well-being, energy, and productivity.